Ma’bulle Tomate : Memori Budaya Aluk Todolo Pada Ritual Kematian di Gandangbatu, Toraja - Ones Kristiani Rapa'; Yurulina Gulo (Universitas Negeri Medan, 2020)
The aim of this paper is to see how changes occur in the rituals of death in Toraja specifically in Gandangbatu. The intended death ritual is the Ma'bulle Tomate ritual. This Ma'bulle Tomate ritual is one of the rituals contained in Rambu Solo. The method used is a qualitative research method with interview and observation techniques. The Ma'bulle Tomate ritual in Gandangbatu has experienced a clear shift in its practice, which in the past in Aluk Todolo beliefs was accompanied by badong, now replaced by singing. the author found that the meaning of badong in Aluk Todolo is as a medium to express the social status of the dead in society, the completeness of the ritual of his death, prayer requests to Puang Matua so that the deceased get a decent place in puya (a place of waiting) and those who live long life and blessed by Puang Matua. While the meaning of the song in Ma'bulle Tomate is the Christian hymn is just a worship of God and comfort to the family. Through the theoretical approach of Massimo Rosati in the book 'Ritual and Sacred' finally can understand and discover how changes occur in the Ma'bulle Tomate Ritual and the meaning of badong in Aluk Todolo before the entry of Christianity in Gandangbatu.